Fe3O4 / Co / CoS2 / surface porous Si composite photoelectric catalytic material as well as preparation method and application thereof

By forming a porous structure on the surface of single crystal Si and modifying the Fe3O4/Co/CoS2 composite powder, the high reflectivity and stability of single crystal Si photocatalytic materials are solved, and the efficiency and stability of photoelectrochemical decomposition of water are improved.

CN119144999AInactive Publication Date: 2024-12-17HUNAN YINGGUANG ENVIRONMENTAL PROTECTION TECH CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411280563.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Single-crystal Si photoelectro-catalytic materials have problems such as high reflectivity, poor stability in wet air and water, and low hydrogen evolution reaction rate, which limits the efficiency of photoelectrochemical decomposition of water.

Method used

The surface porous Si substrate was prepared by metal-assisted etching method, and the Fe3O4/Co/CoS2 composite powder was modified on its surface. The Fe3O4/Co/CoS2/surface porous Si composite material was formed by electroless plating and solvothermal method to reduce the reflectivity. Improve stability and hydrogen evolution reaction rate.

Benefits of technology

It effectively reduces the reflectivity of the material, enhances the light capture effect and stability, accelerates the charge transfer rate, and improves the photocurrent intensity and photocatalytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144999A_ABST
    Figure CN119144999A_ABST
Patent Text Reader

Abstract

The invention discloses a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectric catalytic material as well as a preparation method and application thereof, and belongs to the field of photoelectric catalytic materials. The method comprises the following steps: depositing metal Co on the surface of a surface porous Si base material to form a Co-Si composite material; the Co-Si composite material is added into a sulfur source solution, so that a small amount of Co in the Co-Si composite material is not vulcanized, and the Co / CoS2 / surface porous Si composite photoelectric catalytic material is obtained; and adding the Fe3O4 nanospheres into an ethanol solution, uniformly stirring, and dropwise adding onto the surface of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material to obtain the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material. The surface porous Si substrate is modified through the Fe3O4 / Co / CoS2 composite powder, so that the reflectivity of the material is reduced, and the stability and the hydrogen evolution reaction rate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photoelectric catalytic materials, and in particular relates to a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectric catalytic material and a preparation method and application thereof. Background Art

[0002] Photoelectrocatalytic technology uses solar energy to generate renewable energy. In the process of photoelectrocatalytic reaction, the performance of the catalyst directly affects the efficiency of the reaction. Photoelectrocatalysts mainly include oxynitrides, metal nitrides, metal phosphides, metal vanadates, metal halides, polymers, metal sulfides, metal oxides, Si materials and their corresponding complexes.

[0003] In the prior art, it is a common practice to use single crystal Si materials as photoelectrocatalytic materials. Single crystal Si materials have low material costs, suitable bandgap width, suitable conduction band and valence band positions, so single crystal Si materials show excellent photoelectrochemical water decomposition capabilities. However, from the current research status, there are still many problems with silicon as a photoelectrode. First, silicon has a high light reflectivity, and the part of the incident light that will be reflected is greater than 30%, which restricts the improvement of silicon PEC efficiency; second, silicon has poor stability in humid air and water; third, the hydrogen evolution reaction on the silicon surface is a slow kinetic process. How to solve the above problems is a technical problem that the industry urgently needs to resolve. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the present invention provides a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material and a preparation method and application thereof. The material is prepared by etching planar silicon to form a surface porous Si substrate, and then modifying the surface of the surface porous Si substrate with Fe3O4 / Co / CoS2 composite powder. The surface porous Si substrate is modified by silicon surface modification and Fe3O4 / Co / CoS2 composite powder, thereby reducing the reflectivity of the material, improving the stability and the rate of hydrogen evolution reaction, and effectively solving at least one of the technical problems mentioned in the background technology.

[0005] To solve the above problems, the technical solution of the present invention is:

[0006] A method for preparing a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material comprises the following steps:

[0007] Step 1, preparing a surface porous Si substrate by using a metal-assisted catalytic etching method;

[0008] Step 2, using chemical plating to uniformly deposit a layer of metal Co on the surface of the porous Si substrate to form a Co-Si composite material;

[0009] Step 3, adding the Co-Si composite material to the sulfur source solution, controlling the sulfur content in the sulfur source solution, so that a small amount of Co in the Co-Si composite material is not sulfurized, and obtaining a Co / CoS2 / surface porous Si composite photoelectrocatalytic material;

[0010] Step 4, prepare Fe3O4 nanospheres by solvothermal method, add the prepared Fe3O4 nanospheres into ethanol solution and stir evenly, and then add them dropwise to the surface of Co / CoS2 / surface porous Si composite photoelectrocatalytic material by drop coating method, and then put them into vacuum drying oven and keep them warm at not less than 60°C for at least 12h to obtain Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material.

[0011] As an improvement, step 1 specifically includes the following steps:

[0012] Cut the Si wafer into pieces with an area of ​​1-2 cm 2 The small pieces were then ultrasonically rinsed with acetone for 15 min, ethanol for 10 min, and ultrapure water for 5 min.

[0013] Prepare a mixture of concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1, put the rinsed Si wafer into the mixture, soak it at room temperature for 25 minutes, and then soak it in 5% hydrofluoric acid solution for 2 minutes;

[0014] A solution of 4.65 mol / L HF, 0.01 mol / L AgNO3 and 0.05 mol / L H2O2 was placed in a plastic cup, which was placed in a water bath at a constant temperature of 60°C. The Si wafer was then placed in the mixed solution in the plastic cup for etching.

[0015] The etched Si wafer was soaked in concentrated HNO3 for 1 hour to remove the silver particles on the surface and in the pores. After taking it out, the Si wafer was placed in a drying oven and dried at 70°C for 2 hours to obtain a surface porous Si substrate and weigh it accurately.

[0016] As an improvement, the etching time is 40-50 minutes.

[0017] As an improvement, the plating solution used for chemical cobalt plating is weakly alkaline and includes cobalt salt, hypophosphite and complexing agent, wherein the cobalt salt is selected from at least one of cobalt chloride and cobalt sulfate, the concentration of the plating solution is selected to be 0.01-0.04 mol / L, the hypophosphite is used as a reducing agent, the concentration is selected to be 0.1-0.25 mol / L, and the complexing agent is selected from one of sodium citrate and tetrahydroxypropylethylenediamine THPED, and the concentration is selected to be 0.03-0.09 mol / L; the specific process of chemical cobalt plating includes the following steps:

[0018] The surface porous Si substrate is immersed in a 5-10% HF solution for 2 minutes to remove the surface oxide film, and then rinsed with pure water after being taken out; the rinsed surface porous Si substrate is activated with a PdCl2 solution, and then repeatedly rinsed with pure water after activation; the back of the surface porous Si substrate is adhered with a high temperature resistant and corrosion resistant tape to prevent the deposition of a coating on the back of the surface porous Si substrate, and the surface porous Si substrate is immersed in the plating solution for 5-15 seconds to obtain the required Co plating amount, and then repeatedly rinsed with deionized water after being taken out, and a Co-Si composite material is obtained by drying.

[0019] As an improvement, step 3 specifically includes the following steps:

[0020] The Co-Si composite material was activated and pretreated with dilute strong acid and anhydrous ethanol, and the activated Co-Si composite material was vacuum dried at 60°C for 3h;

[0021] Weigh the mass m of the dried Co-Si composite material, and calculate the mass n of the Co source in the Co-Si composite material;

[0022] Calculate the mass a of sulfur source required to completely react with the mass n of Co source;

[0023] Take a sulfur source with a mass less than a and add it to a mixed solution of 40 mL of deionized water and 40 mL of anhydrous ethanol until the sulfur source is completely dissolved to obtain a colorless transparent solution;

[0024] The dried Co-Si composite material was transferred together with the colorless transparent solution into a 200 mL high-pressure reactor, subjected to solvent thermal reaction at 160-170°C for 6-8 hours, cooled to room temperature, the sample was taken out, and repeatedly washed with deionized water, and then placed in a forced air drying oven at 60°C for 6 hours to obtain a Co / CoS2 / surface porous Si composite material.

[0025] As an improvement, the dilute strong acid is dilute hydrochloric acid, the sulfur source is sulfur-containing organic matter, and the Co content in the Co / CoS2 / surface porous Si composite material is 3%-5% of the CoS2 content.

[0026] As an improvement, the mass ratio of Fe3O4 to Co / CoS2 in the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material is (0:5)-(5:0).

[0027] As an improvement, the preparation process of Fe3O4 nanospheres includes the following steps:

[0028] Weigh 2.5mmol Fe(NO3)2·4H2O and 50mmol NaOH, place them in 50mL ethylene glycol solution, and perform ultrasonic dispersion. After full dissolution, a dark green homogeneous solution is produced. The homogeneous solution is then sealed in an autoclave and reacted at 200℃ for 4h. After cooling to room temperature, the residue is filtered, washed with water, and dried to obtain Fe3O4 nanospheres.

[0029] A Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material is prepared by the above-mentioned preparation method.

[0030] An application of the above-mentioned Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material is used to prepare a photoelectrocatalytic electrode.

[0031] The beneficial effects of the present invention are:

[0032] (1) After etching the plane of single-crystal Si using the metal Ag-assisted etching method, the obtained surface porous Si substrate helps to reduce the Si surface reflectivity and enhance the light capture effect, thereby absorbing more incident light, improving the utilization rate of sunlight, and increasing the photocurrent intensity;

[0033] (2) After the surface porous Si substrate is further modified by metal and metal sulfide, the effective contact area with the electrolyte is increased, which promotes the electrochemical reaction at the electrode / electrolyte interface;

[0034] (3) The Co deposited by chemical plating is evenly distributed, firm and not affected by the shape of the Si surface, overcoming the problem of easy accumulation and shedding when loading by other methods. The heterogeneous structures of the obtained composite materials grow more evenly, more effectively inhibit the recombination of photogenerated charges, accelerate the interface charge transfer rate, and reduce the charge transfer resistance;

[0035] (4) The covered Fe3O4 / Co / CoS2 nanospheres not only protect the surface porous Si, but also reduce the recombination of photogenerated charges and promote the charge transfer between the electrode and the electrolyte to accelerate the photocatalytic process through the formation of heterojunctions between Fe3O4-CoS2, Fe3O4-Si, and CoS2-Si. The material preparation of the present invention also has the characteristics of simple process, mild conditions and high stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It represents the XRD pattern of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample;

[0037] Figure 2 The XPS full spectrum of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample;

[0038] Figure 3 It represents the SEM image of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample at 200μm;

[0039] Figure 4 A comparison chart of the UV-visible diffuse reflectance spectra of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, the planar Si material, the surface porous Si material, the Fe3O4 / surface porous Si composite material and the Co / CoS2 / surface porous Si composite material;

[0040] Figure 5 A diagram showing the light-to-hydrogen conversion efficiency of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials and Fe3O4 / CoS2 / planar Si composite materials at different etching times;

[0041] Figure 6 The light-to-hydrogen conversion efficiency of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material is shown when the mass ratio of Fe3O4 to CoS2 is 0:5, 1:9, 2:8, 3:7, 4:6 and 5:0 respectively;

[0042] Figure 7 A comparison chart showing the light-to-hydrogen conversion efficiency of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, Fe3O4 / Co / CoS2 / planar Si composite photoelectrocatalytic material, Fe3O4 / Co / CoS2 / GCE composite material, surface porous Si material and planar Si material;

[0043] Figure 8 A comparison chart showing the photo-to-hydrogen conversion efficiency of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials under strong light and weak light conditions;

[0044] Fig. 9 A stability curve comparison diagram of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, Fe3O4 / surface porous Si composite material and Co / CoS2 / surface porous Si composite material. DETAILED DESCRIPTION

[0045] In the description of the present invention, it is necessary to understand that the terms indicating orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred elements must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0046] The embodiments of the present invention are further described below in conjunction with the accompanying drawings.

[0047] Example 1

[0048] This embodiment provides a method for preparing a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, comprising the following steps:

[0049] Step 1: Prepare a surface porous Si substrate using a metal-assisted catalytic etching method.

[0050] Step 1 specifically includes the following steps:

[0051] The Si wafer was cut into pieces with an area of ​​2 cm 2 The small pieces were then ultrasonically rinsed with acetone for 15 min, ethanol for 10 min, and ultrapure water for 5 min.

[0052] Prepare a mixture of concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1, put the rinsed Si wafer into the mixture, soak it at room temperature for 25 minutes, and then soak it in 5% hydrofluoric acid solution for 2 minutes;

[0053] A solution of 4.65 mol / L HF, 0.01 mol / L AgNO3 and 0.05 mol / L H2O2 was placed in a plastic cup, which was placed in a water bath at a constant temperature of 60°C. The Si wafer was then placed in the mixed solution in the plastic cup for etching.

[0054] The etched Si wafer was soaked in concentrated HNO3 for 1 hour to remove the silver particles on the surface and in the pores. After taking it out, the Si wafer was placed in a drying oven and dried at 70°C for 2 hours to obtain a surface porous Si substrate and weigh it accurately.

[0055] In order to ensure that dense and fine pores are completely formed on the surface of the Si wafer and to prevent the fine pores from being destroyed due to excessive etching, the etching time is selected to be 45 minutes.

[0056] Step 2: uniformly depositing a layer of metal Co on the surface of the porous Si substrate by chemical plating to form a Co-Si composite material.

[0057] The plating solution used for chemical cobalt plating is based on cobalt salt and hypophosphite, and is prepared by adding suitable complexing agents and other additives such as stabilizers, accelerators, surfactants, etc. The solution is weakly alkaline. In the plating solution, the cobalt salt is selected from at least one of cobalt chloride and cobalt sulfate, and the concentration of the plating solution is selected to be 0.03 mol / L. The hypophosphite is used as a reducing agent, and the concentration is selected to be 0.2 mol / L. The complexing agent is selected as sodium citrate, and the concentration is selected to be 0.05 mol / L. The specific process of chemical cobalt plating includes the following steps:

[0058] The surface porous Si substrate is immersed in a 6% HF solution for 2 minutes to remove the surface oxide film, and is rinsed with pure water after being taken out; the rinsed surface porous Si substrate is activated with a PdCl2 solution, and is repeatedly rinsed with pure water after activation; the back of the surface porous Si substrate is adhered with a high temperature resistant and corrosion resistant tape to prevent the deposition of a coating on the back of the surface porous Si substrate, the surface porous Si substrate is immersed in the plating solution for 12 seconds to obtain the required Co plating amount, and is repeatedly rinsed with deionized water after being taken out, and a Co-Si composite material is obtained by drying.

[0059] Step 3, adding the Co-Si composite material to the sulfur source solution, controlling the sulfur content in the sulfur source solution, so that a small amount of Co in the Co-Si composite material is not sulfurized, and obtaining a Co / CoS2 / surface porous Si composite photoelectrocatalytic material.

[0060] Step 3 specifically includes the following steps:

[0061] The Co-Si composite material was activated and pretreated with dilute strong acid and anhydrous ethanol, and the activated Co-Si composite material was vacuum dried at 60°C for 3h;

[0062] Weigh the mass m of the dried Co-Si composite material, and calculate the mass n of the cobalt source in the Co-Si composite material;

[0063] Calculate the mass a of sulfur source required to completely react with the mass n of cobalt source;

[0064] Take a sulfur source with a mass less than a and add it to a mixed solution of 40 mL of deionized water and 40 mL of anhydrous ethanol until the sulfur source is completely dissolved to obtain a colorless transparent solution;

[0065] The dried Co-Si composite material was transferred together with the colorless transparent solution into a 200 mL high-pressure reactor, subjected to solvothermal reaction at 160°C for 8 h, cooled to room temperature, the sample was taken out, and repeatedly washed with deionized water, then placed in a forced air drying oven at 60°C for 6 h to obtain a Co / CoS2 / surface porous Si composite material.

[0066] The dilute strong acid may be dilute hydrochloric acid, and the sulfur source may be sulfur-containing organic matter, such as mercaptans, thiophenols, sulfides, disulfides, thioureas, and the like.

[0067] It should be noted that the values ​​of m and n can be adjusted year-on-year according to actual test conditions, and the value of a can be adjusted according to the type of sulfur source, which is not limited in this embodiment.

[0068] Preferably, in the Co / CoS2 / surface porous Si composite material, the content of Co is 3%-5% of the content of CoS2. Since a small amount of Co is not sulfided, two effective components, Co and CoS2, exist in the composite material at the same time. Co and CoS2 have different catalytic activities and selectivities, and can produce a synergistic effect when used in combination to improve the catalytic efficiency. Co, as a metallic material, easily reacts with other substances during the catalytic process and loses its activity, while CoS2, as an inorganic compound, has high stability. Therefore, the present invention selects a large amount of CoS2 combined with a small amount of Co in the form of ensuring the diversification of catalytic activity, which can keep the composite material stable and thus maintain the catalytic activity.

[0069] Step 4, prepare Fe3O4 nanospheres by solvothermal method, add the prepared Fe3O4 nanospheres into ethanol solution and stir evenly, and then add them dropwise to the surface of Co / CoS2 / surface porous Si composite photoelectrocatalytic material by drop coating method, and then put them into vacuum drying oven and keep them warm at not less than 60°C for at least 12h to obtain Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material.

[0070] In the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, the mass ratio of Fe3O4 to Co / CoS2 is (0:5)-(5:0), preferably 2:8. The amount of Fe3O4 nanospheres added can be determined according to the number of dropwise additions.

[0071] The preparation process of Fe3O4 nanospheres includes the following steps:

[0072] Weigh 2.5mmol Fe(NO3)2·4H2O and 50mmol NaOH, put them in 50mL ethylene glycol solution, stir them with ultrasonic wave, and produce a dark green homogeneous solution after full dissolution. Then seal the homogeneous solution in an autoclave (100mL), react at 200℃ for 4h, cool to room temperature, filter the residue, wash with water, and dry to obtain Fe3O4 nanospheres.

[0073] Example 2

[0074] This embodiment provides a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, which is prepared by the preparation method of Example 1.

[0075] Figure 1 The XRD pattern of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample in this embodiment is shown in FIG. Figure 1It can be seen that the diffraction peaks at 2θ of 18.2°, 30.1°, 35.4°, 43.1°, 53.4°, 57.0° and 62.6° correspond to the (111), (220), (311), (400), (422), (511) and (440) crystal planes of Fe3O4 (JCPDS No. 19-0629); the diffraction peaks at 2θ of 27.9°, 32.3°, 36.2°, 39.8°, 46.3°, 49.3°, 54.9°, 60.2° and 62.7° correspond to the (111), (220), (311), (400), (422), (511) and (440) crystal planes of CoS2 (JCPDS The diffraction peak at 2θ of 69.3° corresponds to the (400) crystal plane of single crystal Si (JCPDS No.80-0018).

[0076] Figure 1 In the system, diffraction peaks of Fe3O4, CoS2 and Si appear simultaneously. However, due to the low content of Co in the system, no diffraction peak of Co is found. Figure 1 The results show that the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material was correctly prepared. The peaks of Fe3O4 and CoS2 did not affect each other, the diffraction peak intensity remained at a high level, and did not affect the strong diffraction peak of Si.

[0077] Figure 2 The XPS spectrum of the Fe3O4 / Co / CoS2 / surface porous Si composite material sample in this embodiment is shown in FIG. Figure 2 It can be seen that Fe, O, Co, S and Si elements exist in the sample, which can also be used to prove the successful preparation of Fe3O4 / Co / CoS2 / surface porous Si composite materials.

[0078] Figure 3 The SEM image of the Fe3O4 / Co / CoS2 / surface porous Si composite material sample at 200 μm is shown. Figure 1 It can be seen that there are many pores on the surface of the Si substrate, and octahedral nanoparticles and nanospheres are evenly distributed around the pores. The nanospheres and nanoparticles are not aggregated separately, but embedded in each other. This combination helps promote the migration of carriers and has good dispersion, which can provide more reactive sites to improve the photoelectrochemical performance. In addition, the octahedral nanoparticles also provide a path for the refraction of light. The combination of the pore structure and the octahedral structure with the nanosphere structure minimizes the surface reflectivity of the Si substrate.

[0079] The Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material provided in this embodiment is compared with the planar Si material, the surface porous Si material, the Fe3O4 / surface porous Si composite material and the Co / CoS2 / surface porous Si composite material, and the UV-visible diffuse reflectance spectra of each material are obtained by testing. Figure 4 As shown, from Figure 4 It can be seen that the reflectivity of the planar Si material is greater than that of the surface porous Si material. This is because there is a porous array structure on the surface of the surface porous Si material. The incident light in the hole undergoes multiple continuous reflections, absorbs photons and reduces the overall light intensity. The reflectivity of the Co / CoS2 / surface porous Si material and the Fe3O4 / surface porous Si composite material are both lower than that of the surface porous Si material. The reason is that the shape of the loaded Co / CoS2 nanoparticles is an octahedral structure, which can increase the refraction path of the incident light and enhance light absorption. Therefore, the Co / CoS2 / surface porous Si material has a lower reflectivity than the surface porous Si material, and the black Fe3O4 nanospheres loaded on the Fe3O4 / surface porous Si material have a light shielding effect, so the Fe3O4 / surface porous Si material also has a lower reflectivity than the surface porous Si material. The reflectivity of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material is at the lowest level among all materials. It is precisely because of the combination of the above two principles that the light absorption effect is greatly enhanced and the reflectivity is reduced.

[0080] Example 3

[0081] This embodiment provides an application of a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material for preparing a photoelectrocatalytic electrode.

[0082] The preparation process of the photoelectrocatalytic electrode includes the following steps:

[0083] The samples were prepared using Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials;

[0084] A layer of metallic indium is covered on the back of the sample, and then the copper core wire is fixed on the indium layer with tin wire, and the back and sides of the sample are wrapped with Kraft sealant to ensure that only the front side is in contact with the electrolyte to complete the preparation.

[0085] The improvement of the photoelectric performance of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material mainly depends on the Fe3O4 / Co / CoS2 powder attached to the surface, and the adhesion ability of the Fe3O4 / Co / CoS2 powder is closely related to the pores on the surface of the surface porous Si substrate. Therefore, it is necessary to verify the influence of the pores on the surface of the surface porous Si substrate on the photoelectric performance of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material. The formation of the pores is controlled by the etching time. Figure 5 The photo-hydrogen conversion efficiency diagram of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material and Fe3O4 / CoS2 / planar Si composite material at different etching times is shown. Figure 5 It can be seen that under different etching times, the photo-hydrogen conversion efficiency of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials is always higher than that of Fe3O4 / CoS2 / planar Si composite materials, indicating that compared with planar Si materials, the surface porous Si materials after etching have better photoelectrochemical water splitting performance. The photo-hydrogen conversion efficiency of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials obtained with an etching time of 45 min is as high as 0.981%, which is better than the etching time of 40 min and 50 min. The reason is that if the etching time is too short, the surface structure of the pores is incomplete, and the reflectivity of the Si substrate is still at a high level, resulting in low light absorption performance; if the etching time is too long, the pores on the surface of the Si substrate are damaged, resulting in fewer light refraction paths, and more incident light is reflected into the air, which has a greater impact on the photoelectrochemical performance of the composite material. Therefore, it is necessary to reasonably select the etching time according to the test results, for example, 45 min.

[0086] The effects of Fe3O4 and Co / CoS2 on the photoelectric properties of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials have different principles. Different ratios of the two will lead to differences in the photoelectric properties of the samples. Therefore, it is necessary to verify the effect of the ratio of Fe3O4 and Co / CoS2 on the photoelectric properties of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials. Figure 6 The photo-to-hydrogen conversion efficiency of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials is shown in the figure when the mass ratio of Fe3O4 and Co / CoS2 is 0:5, 1:9, 2:8, 3:7, 4:6 and 5:0 respectively. Figure 6It can be seen that under the above mass, the photo-hydrogen conversion efficiency of the samples is 0.502%, 0.749%, 0.981%, 0.509%, 0.327% and 0.33% respectively. The photoelectric performance of the sample under pure Fe3O4 is poor, which is caused by the shielding effect of Fe3O4, and the photoelectric performance of the sample under pure Co / CoS2 is also poor, which is caused by the stability of CoS2 in Co / CoS2. When the two are compounded in proportion, the photoelectric performance gradually increases, and the photoelectric performance reaches the best when the compound ratio is 2:8, and then gradually decreases. This is because the shielding effect is also enhanced with the increase in the amount of Fe3O4, resulting in a decrease in photoelectric performance. Only when the ratio of the two is 2:8, can the respective roles of the three and the synergistic effect between the three be better displayed, which can not only play the protective role of Fe3O4, but also reflect the light absorption performance of Co / CoS2 and surface porous Si.

[0087] In order to verify the photoelectric performance of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material in this embodiment, it was compared with the Fe3O4 / Co / CoS2 / planar Si composite photoelectrocatalytic material, the Fe3O4 / Co / CoS2 / GCE composite material, the surface porous Si material, and the planar Si material. Figure 7 The figure shows the light-to-hydrogen conversion efficiency of the above materials. Figure 7 It can be seen that the photohydrogen conversion efficiency of the planar Si material is relatively low, indicating that its photoelectrochemical performance is relatively poor, and whether it is formed by loading other materials or etching to form a surface porous Si material, the photohydrogen conversion efficiency is doubled. Compared with other materials, the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material provided in this embodiment has a greatly improved photoelectric performance, which is due to the combination of the loaded Fe3O4 / Co / CoS2 powder and the surface porous Si substrate.

[0088] In order to verify the effect of light on the photoelectric performance of Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic materials, the light-to-hydrogen conversion efficiency curves of the samples under strong and weak light conditions were measured, such as Figure 8 As shown, from Figure 8 It can be seen that the maximum photo-hydrogen conversion efficiency of the sample under strong light is as high as 0.981%, while the photo-hydrogen conversion efficiency of the sample under weak light is only 0.00899%. From the above analysis, it can be seen that the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material provided in this embodiment has good photoelectric performance under strong light conditions, indicating that it can be well applied to the photoelectrocatalytic process.

[0089] In order to verify the stability of the Fe3O4 / Co / CoS2 / porous Si composite photoelectrocatalytic material in this embodiment, it was compared with the Fe3O4 / porous Si composite material and the Co / CoS2 / porous Si composite material. Fig. 9 The stability curves of the above materials are shown in Figure 2. Fig. 9 It can be seen that the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material has achieved the best stability. The reason is that the combination of porous Si sheets, Fe3O4 nanospheres and Co / CoS2 nanoparticles, the synergistic effect of the three is conducive to reducing the reflectivity, providing a larger contact area between the photoelectrode and the electrolyte, and accelerating the surface reaction kinetics; the protective layer of Fe3O4 prevents Si from being corroded and enhances the stability of the photoelectrode. However, the three photoelectrodes all dropped rapidly at the beginning, mainly because the photogenerated holes have not yet reached the electrode to participate in the oxidation of water molecules, resulting in a sharp drop in the photocurrent density.

[0090] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, characterized in that: The steps include: Step 1, preparing a surface porous Si substrate by using a metal-assisted catalytic etching method; Step 2, using chemical plating to uniformly deposit a layer of metal Co on the surface of the porous Si substrate to form a Co-Si composite material; Step 3, adding the Co-Si composite material to the sulfur source solution, controlling the sulfur content in the sulfur source solution, so that a small amount of Co in the Co-Si composite material is not sulfurized, and obtaining a Co / CoS2 / surface porous Si composite photoelectrocatalytic material; Step 4, prepare Fe3O4 nanospheres by solvothermal method, add the prepared Fe3O4 nanospheres into ethanol solution and stir evenly, and then add them dropwise to the surface of Co / CoS2 / surface porous Si composite photoelectrocatalytic material by drop coating method, and then put them into vacuum drying oven and keep them warm at not less than 60°C for at least 12h to obtain Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material.

2. The method for preparing the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 1, characterized in that: Step 1 specifically includes the following steps: Cut the Si wafer into pieces with an area of ​​1-2 cm 2 The small pieces were then ultrasonically rinsed with acetone for 15 min, ethanol for 10 min, and ultrapure water for 5 min. Prepare a mixture of concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1, put the rinsed Si wafer into the mixture, soak it at room temperature for 25 minutes, and then soak it in 5% hydrofluoric acid solution for 2 minutes; A solution of 4.65 mol / L HF, 0.01 mol / L AgNO3 and 0.05 mol / L H2O2 was placed in a plastic cup, which was placed in a water bath at a constant temperature of 60°C. The Si wafer was then placed in the mixed solution in the plastic cup for etching. The etched Si wafer was soaked in concentrated HNO3 for 1 hour to remove the silver particles on the surface and in the pores. After taking it out, the Si wafer was placed in a drying oven and dried at 70°C for 2 hours to obtain a surface porous Si substrate and weigh it accurately.

3. The method for preparing the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 2, characterized in that: The etching time is 40-50 minutes.

4. The method for preparing the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 1, characterized in that: The plating solution used for chemical cobalt plating is weakly alkaline and includes cobalt salt, hypophosphite and complexing agent, wherein the cobalt salt is selected from at least one of cobalt chloride and cobalt sulfate, the concentration of the plating solution is selected to be 0.01-0.04 mol / L, the hypophosphite is used as a reducing agent, the concentration is selected to be 0.1-0.25 mol / L, and the complexing agent is selected from one of sodium citrate and tetrahydroxypropylethylenediamine THPED, and the concentration is selected to be 0.03-0.09 mol / L; the specific process of chemical cobalt plating includes the following steps: The surface porous Si substrate is immersed in a 5-10% HF solution for 2 minutes to remove the surface oxide film, and then rinsed with pure water after being taken out; the rinsed surface porous Si substrate is activated with a PdCl2 solution, and then repeatedly rinsed with pure water after activation; the back of the surface porous Si substrate is adhered with a high temperature resistant and corrosion resistant tape to prevent the deposition of a coating on the back of the surface porous Si substrate, and the surface porous Si substrate is immersed in the plating solution for 5-15 seconds to obtain the required Co plating amount, and then repeatedly rinsed with deionized water after being taken out, and a Co-Si composite material is obtained by drying.

5. The method for preparing the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 1, characterized in that: Step 3 specifically includes the following steps: The Co-Si composite material was activated and pretreated with dilute strong acid and anhydrous ethanol, and the activated Co-Si composite material was vacuum dried at 60°C for 3h; Weigh the mass m of the dried Co-Si composite material, and calculate the mass n of the Co source in the Co-Si composite material; Calculate the mass a of sulfur source required to completely react with the mass n of Co source; Take a sulfur source with a mass less than a and add it to a mixed solution of 40 mL of deionized water and 40 mL of anhydrous ethanol until the sulfur source is completely dissolved to obtain a colorless transparent solution; The dried Co-Si composite material was transferred together with the colorless transparent solution into a 200 mL high-pressure reactor, subjected to solvent thermal reaction at 160-170°C for 6-8 hours, cooled to room temperature, the sample was taken out, and repeatedly washed with deionized water, and then placed in a forced air drying oven at 60°C for 6 hours to obtain a Co / CoS2 / surface porous Si composite material.

6. The method for preparing the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 5, characterized in that: The dilute strong acid is dilute hydrochloric acid, the sulfur source is sulfur-containing organic matter, and the content of Co in the Co / CoS2 / surface porous Si composite material is 3%-5% of the content of CoS2.

7. The method for preparing the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 1, characterized in that: In the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, the mass ratio of Fe3O4 to Co / CoS2 is (0:5)-(5:0).

8. The method for preparing the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 1, characterized in that: The preparation process of Fe3O4 nanospheres includes the following steps: Weigh 2.5mmol Fe(NO3)2·4H2O and 50mmol NaOH, place them in 50mL ethylene glycol solution, and perform ultrasonic dispersion. After full dissolution, a dark green homogeneous solution is produced. The homogeneous solution is then sealed in an autoclave and reacted at 200℃ for 4h. After cooling to room temperature, the residue is filtered, washed with water, and dried to obtain Fe3O4 nanospheres.

9. A Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. An application of the Fe3O4 / Co / CoS2 / surface porous Si composite photoelectrocatalytic material as claimed in claim 9, characterized in that: Used to prepare photoelectrocatalytic electrodes.

Citation Information

Patent Citations

  • CoS2 / CoS2-NC catalytic electrode material with three-dimensional core-shell structure as well as preparation method and application of catalytic electrode material

    CN109913895A

  • Preparation method of cobalt disulfide microspheres with water photolysis oxygen production catalysis assisting function

    CN110605132A

  • CsPW11Fe / Si heterojunction composite photoelectric material and preparation method thereof

    CN110707164A

  • CoP / Si hydrogen evolution catalysis material and preparation method thereof

    CN110882707A

  • Preparation of cobalt-cobalt disulfide heterojunction embedded nitrogen-sulfur co-doped carbon nanocage positive electrode material and application of cobalt-cobalt disulfide heterojunction embedded nitrogen-sulfur co-doped carbon nanocage positive electrode material in lithium-sulfur battery

    CN116504951A